1975
DOI: 10.1099/0022-1317-27-3-329
|View full text |Cite
|
Sign up to set email alerts
|

Early Alteration of Poliovirus in Infected Cells and Its Specific Inhibition

Abstract: SUMMARYHeLa cells infected with radioactive poliovirus type 2 were disrupted with ultrasonic treatment, followed by addition of a non-ionic detergent. Two types of virus particles were found to sediment at 80 to 90 ~o the rate of native virus. The first of these appeared to be a complex of native virus particles and membrane components, since treatment with o-2 ~ SDS released infectious native particles. The second was non-infectious and its sedimentation rate was not greatly altered by SDS. One hour after inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(82 citation statements)
references
References 13 publications
6
76
0
Order By: Relevance
“…However, attempts to/abel the cellular component(s) associated with the modified virus particles, either by using cells pre-labelled with radioactive amino acids and 32p or by iodinating the isolated complex have been unsuccessful. This situation is similar to that described by Lonberg-Holm et al (1975) who found that poliovirus recovered from HeLa cells infected in the presence ofa methylthiopyrimidine $7, a compound which allows attachment but prevents uncoating ofpoliovirus by HeLa cells, was associated with cellular components and had a reduced sedimentation coefficient and specific infectivity. However, these cellular components could be removed from the poliovirus complex by treatment with detergents.…”
Section: Cellular Location Of Disrupted Virussupporting
confidence: 68%
See 1 more Smart Citation
“…However, attempts to/abel the cellular component(s) associated with the modified virus particles, either by using cells pre-labelled with radioactive amino acids and 32p or by iodinating the isolated complex have been unsuccessful. This situation is similar to that described by Lonberg-Holm et al (1975) who found that poliovirus recovered from HeLa cells infected in the presence ofa methylthiopyrimidine $7, a compound which allows attachment but prevents uncoating ofpoliovirus by HeLa cells, was associated with cellular components and had a reduced sedimentation coefficient and specific infectivity. However, these cellular components could be removed from the poliovirus complex by treatment with detergents.…”
Section: Cellular Location Of Disrupted Virussupporting
confidence: 68%
“…The fate of picornaviruses after they have attached to host cells has been studied with poliovirus (Joklik & Darnell, 1961 ;Fenwick & Cooper, I962;Holland, 1962;Mandel, I962a, b;Lonberg-Holm et aL 1975;De Sena & Mandel, 1976, I977), Coxsackie B 3 virus (Crowell et al I971), the cardioviruses (Hall & Rueckert, 1971) and rhinoviruses (Lonberg-Holm & Korant, 1972;Lonberg-Holm & Noble-Harvey, 1973;Noble & Lonberg-Holm, 1973). Although previous studies of the early interaction of FMDV with pig kidney cells were made before purified radioactive virus was available (Brown et al 1961(Brown et al , 1962Thorne, 1962) so that a precise study of the early events was difficult, it was ascertained that the I4oS virus particles were rapidly broken down to the virus RNA and a 12S sub-unit.…”
Section: Introductionmentioning
confidence: 99%
“…Heating virions or 'A' particles at 37 °C also has produced 80S particles, as has been found for poliovirus (Breindl, 1971). In addition, particles which sedimented more slowly than 'A' particles have been recognized in poliovirus-infected cell extracts (Lonberg-Holm et al, 1975;Fenwick & Wall, 1973) and in in vitro uncoating systems (DeSena & Torian, 1980). Nevertheless, their significance in the pathway to infection has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…The poliovirus receptor has been cloned and identified as a member of the immunoglobulin supergroup (Mendelsohn, Wimmer & Racaniello, 1989), but its function in the human host has not yet been identified. For these viruses, interaction with the cellular receptor initiates changes in the viral capsid that have been associated with the first step in viral uncoating (Everaert, Vrijsen & Boeyr, 1989;Fricks & Hogle, 1990;Lonberg-Holm, Gosser & Kauer, 1975;Kaplan, Freistadt & Racaniello, 1990). This involves release of VP4 with formation of the A particle, a non-infectious particle with a reduced sedimentation coefficient that is considerably more hydrophobic than the native virion, probably due to extrusion of the amino terminus of VP1 (DeSena & Mandell, 1977;Fricks & Hogle, 1990;Gomez Yafal, Kaplan, Racaniello & Hogle, 1993) (Fig.…”
Section: Introductionmentioning
confidence: 99%